IRITABLE BOWEL SYNDROME AS THE FIRST MANIFESTATION OF HASHIMOT'S TIROIDITIS - Jandrić-Kočić, Marijana C (PONS - medicinski časopis, 2021)
Introduction: Hashimoto's thyroiditis has a complex effect on the gastrointestinal tract, which includes hormone receptor alteration, neuromuscular disorders, myopathies caused by intestinal wall infiltration.                                                                                                                Case report: A patient born in 1976 due to moderate pain in the lower abdomen present backwards for three months, which intensifies before defecation and immediately after the same discount, occurs in the outpatient clinic. There are two to four fluid stools daily in which he did not notice the presence of mucus or blood. It negates earlier illnesses as well as diseases relevant to heredity. Physical examination provides a neat finding. Ultrasound examination of the abdomen within the age range. Thyroid ultrasound (Krupa Health Center at Uni) identifies the right flap of a 48x24x10 diametre with hypoechogenic calcified nodus 14x12 mm in diameter (meets the criteria of the American Thyroid Association for aspiration biopsy), left flap of 44x20x14 mm diameter. The following are the laboratory findings: TSH 7.66 mIU / l, FT4 6.42 pmol / l, TG 5080 ng / ml, Calcitonin 8.94 pg / ml, TG-At 24.99 Iu / ml, TPO-At 500 Iu / ml. The patient is instructed on a hygienic dietary regimen and includes spasmolytic and antidiarrheal, and referred to a nuclear medicine specialist who performs an aspiration biopsy (TBSRTC IV follicular tumor). The Oncology Consilium indicates surgery (right-sided lobectomy) with ex-tempore verification and further follow-up. Pathohistological examination of the removed right lobe excludes the presence of malignant disease (struma coloides multinodosa glandulae thyroideae). Antidiarrheal therapy is discontinued and replacement therapy is administered (Levothyroxine sodium tablets 50 mcg 1x1 tablets). Subsequent proctosigmoidoscopy shows a neat finding. One year after surgery the patient is in remission of the disease.                                                                                                                                                                    Conclusion: Diagnostic evaluation of the thyroid gland in patients with irritable colon syndrome significantly improves quality of life, reduces occupational absenteeism and health care costs
Keywords: autoimmune, thyroiditis, hypothyroidism, syndrome, irritable, colon